Plant regeneration and floral bud formation from intact floral parts of African violet (Saintpaulia ionantha H. Wendl.) cultured in vitro - Daud, N.; Taha, R.M. (2008)
Intact immature flower buds of African violet (Saintpaulia ionantha II. Wendl.) were used as explant sources for in vitro studies. The effect of exogenous hormones, NAA and BAP on the indirect organogenesis of this species was observed. Callus was formed on the cut end (base) of pedicels of floral buds where they were in contact with the medium. When maintained on the same medium, callus was differentiated into adventitious shoots after 10 weeks in culture. MS media supplemented with 2.0 mg L-1 NAA and 1.0 mg L-1 BAP gave the highest number of sterile or vegetative floral buds from the surface of callus of the explants, but these buds failed to develop further. The floral buds were expanded as abnormal flowers. The floral structures were smaller in size compared to intact flowers. Petals (corolla) were white to purple in colour but did not form any reproductive organs i.e., stamens or pistils. All sterile or vegetative floral buds and abnormal flowers survived for 3 months in culture but failed to reach anthesis. Â© 2008 Asian Network for Scientific Information.